GAO cites FAA security breaches. - Bettelheim, Adriel (CQ Weekly, 2000)
A General Accounting Office (GOA) report maintains that the Federal Aviation Administration (FAA) failed to run security checks on foreign citizens employed to debug the U.S. air-traffic control system. The report for the House Science Committee, which released on January 3, 2000, highlighted the fact that critical computer codes could be analyzed for weaknesses, exposing the air-traffic system to intrusion and malicious attacks.